Mothership versus drip and ship for thrombectomy in patients who had an acute stroke: a systematic review and meta-analysis. (8th October 2018) - Ismail, Mohammad; Armoiry, Xavier; Tau, Noam; Zhu, François; Sadeh-Gonik, Udi; Piotin, Michel; Blanc, Raphael; Mazighi, Mikaël; Bracard, Serge; Anxionnat, René; Schmitt, Emmanuelle; Mione, Gioia; et al.
Abstract : Background: The effectiveness of mechanical thrombectomy (MT) in acute ischemic stroke due to large vessel occlusion is time-dependent. While only stroke centers with endovascular capabilities perform MT, many patients who had a stroke initially present to the closest primary stroke centers capable of administering earlier intravenous thrombolysis, and then require to be transferred to a comprehensive stroke center for MT. Purpose: To compare the outcomes of this care pathway (drip and ship (DS)) with that whereby patients are directly transferred to a comprehensive stroke center (mothership (MS)). Methods: We performed a systematic review and meta-analysis of published studies using several electronic databases to determine whether successful reperfusion (modified Thrombolysis In Cerebral Infarction ≥2b), functional independence at 90 days (modified Rankin Scale score ≤2), symptomatic intracranial hemorrhage, and 90-day mortality differed between those who underwent MT with the DS or the MS treatment pathway. Outcomes were meta-analyzed and the results expressed as adjusted relative risk (aRR) for the primary analysis and unadjusted relative risk (uRR) for secondary analysis. Results: Eight studies including 2068 patients were selected, including one study reporting results fully adjusted for baseline characteristics. Patients undergoing MS had better functional independence than those undergoing DS (uRR=0.87, 95% CI 0.81 to 0.93; aRR=0.87, 95% CI 0.77 to 0.98). No difference was found between the treatment pathways in successful reperfusion (uRR=1.05, 95% CI 0.95 to 1.15; aRR=1.00, 95% CI 0.92 to 1.10), symptomatic intracranial hemorrhage (uRR=1.37, 95% CI 0.91 to 2.06; aRR, 1.53, 95% CI 0.79 to 2.98), and 90-day mortality (uRR=1.00, 95% CI 0.84 to 1.19; aRR=1.21, 95% CI 0.89 to 1.64). Conclusions: Patients who had an acute ischemic stroke admitted directly to a comprehensive stroke center (MS patients) with endovascular capacities may have better 90-day outcomes than those receiving DS treatment. However, major limitations of current evidence (ie, retrospective studies and selection bias) suggest a need for adequately powered studies. Multicenter randomized controlled trials are expected to answer this question.